Spindle's end - McKinley, Robin (Firebird, 2002)
The infant princess Briar Rose is cursed on her name day by Pernicia, an evil fairy, and then whisked away by a young fairy to be raised in a remote part of a magical country, unaware of her real identity and hidden from Pernicia's vengeful powers.